INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND PRICE ON THE PURCHASE DECISION OF IPHONE HDC (HANDPHONE COPY DRAW) TO STIE DEVELOPMENT STUDENTS - Benhart Nainggolan; Rodi Syafrizal (RADJA PUBLIKA, 2023)
This study aims to determine the effect of product quality, brand image and price on purchasing decisions for iPhone HDC (Mobile Copy Draw) for STIE Bina Karya students. The research method used is a quantitative method using SPSS version 25.00. The data collected from the results of distributing questionnaires were 41 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely the T test. Y), the brand image variable (X2) has no effect on the purchasing decision variable (Y), Price (X3) has an effect on purchasing decisions (Y) and product quality (X1),.